1999
DOI: 10.1097/00005392-199909000-00057
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Urodynamic Evaluation After Ureterocystoplasty With Different Amounts of Tissue

Abstract: There is a difference in median increased bladder capacity when a segment of distal ureter is used to augment the bladder versus 1 or 2 whole ureters. However, the use of distal ureter still represents a safe alternative for augmenting the bladder and simultaneously resolving massive reflux. Ureterocystoplasty is an excellent choice for increasing bladder capacity and improving bladder compliance despite the different amounts of tissue available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Only 1 (6.3%) patient in the series of Churchill et al [6]could void spontaneously. Similarly 80% of the patients the series of Gosalbez and Kim [7]and 91% of the cases in the series of Zubieta et al [14]were on CIC. Fifty–seven percent of our patients also performed CIC.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Only 1 (6.3%) patient in the series of Churchill et al [6]could void spontaneously. Similarly 80% of the patients the series of Gosalbez and Kim [7]and 91% of the cases in the series of Zubieta et al [14]were on CIC. Fifty–seven percent of our patients also performed CIC.…”
Section: Discussionmentioning
confidence: 91%
“…We used a similar technique for ureterocystoplasty in our patients using both ureters to provide enough tissue for successful bladder augmentation. Recently Zubieta et al [14]reported the largest series of ureterocystoplasty with 32 patients. Transureteroureterostomy was performed in 11 cases to preserve the ipsilateral kidney and 7 cases in this group also underwent Cohen reimplantation [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations